A new challenge in the DEM/FEM simulation of the shot peening process: The residual stress field at a sharp edge. (1st March 2020) - Marini, M.; Piona, F.; Fontanari, V.; Bandini, M.; Benedetti, M.
Highlights: Reconstruction of residual stresses near sharp edge using experimental measurements. Set up of realistic discrete element model of shot peening and nozzle on a flat surface. Discrete element simulation of shot peening on a sharp edge. Realistic and simplified finite element models. Explicit dynamic finite element simulation of shot peening on edge. Abstract: Shot peening (SP) is used to enhance the fatigue life of metallic components. The knowledge of the resulting residual stress (RS) field in the vicinity of geometrical features working as stress raisers is essential to fully integrate SP into the design stage, but is of very difficult achievement, both from a numerical and experimental standpoint. Finite elements (FE) proved to be a powerful tool for tuning the SP process and predicting the RSs, and Discrete element (DE) simulations can be used to study the dynamics of peening particles, especially in the vicinity of geometrical features. A synergistic approach (DEM-FEM) can be effective to study the effects of SP near edges or notches. This paper explores the potentiality of DEM-FEM to simulate SP on an edge. The micro-SP treatment with ceramic beads on the aluminum alloy Al-7075-T651 is considered. DE simulations are devised to study the steady state of the SP nozzle and to predict the impact velocity of the shots when the nozzle approaches and turns around the edge. These data are used to set up explicit dynamic FE simulations of the SP in the immediate vicinity of the edge, keeping into account the stochastic nature of the SP process. The resulting RS field is compared to the RS field computed using thermal fields in a FEM simulation, calibrated with experimental data, from XRD analysis.